Coupling and Interlayer Exciton in Twist‐Stacked WS2 Bilayers. Issue 11 (17th August 2015) - Zheng, Shoujun; Sun, Linfeng; Zhou, Xiaohao; Liu, Fucai; Liu, Zheng; Shen, Zexiang; Fan, Hong Jin
Abstract : Interlayer electronic and mechanical couplings of transitional metal dichalcogenides due to Van der Waals force determine their band structure and Raman modes evolution, respectively. Twist‐stacked WS2 bilayers have been synthesized with twist angles of 0°, 13°, 30°, 41°, 60°, and 83° via chemical‐vapor depositon, which allows us to study the coupling effect by Raman and photoluminescence spectroscopy and density function calculation. The photoluminescence property implies that these random‐twisted WS2 bilayers behave as quasi‐direct bandgap material due to weakened interlayer coupling as a result of larger interlayer distances than the nontwisted 0° and 60° stacked WS2 bilayers (with an indirect band gap). In addition, an additional small peak (AI ) near the excitonic transition peak (A) is observed from the twisted bilayers, which can be attributed to the interlayer exciton transition. Abstract : WS2 bilayers with different twist angles are observed in high‐temperature chemical vapor deposition growth. The random twisted WS2 bilayers show enhanced photoluminescence and absence of the indirect transition peak, which is due to weakened interlayer coupling as a result of larger interlayer distances than the nontwisted AA and AB stacking bilayers.